The twilight of sovereignty - Wriston, Walter B. (Scribner, 1992)
The author of Risk and Other Four Letter Words examines instant global electronic information and its impact on humanity, showing that the marriage of global TV, mobile telephones, satellites, and faxes with computers comprises a new geopolitical revolution.